2011
DOI: 10.1074/jbc.m111.281659
|View full text |Cite
|
Sign up to set email alerts
|

HIV ENV Glycoprotein-mediated Bystander Apoptosis Depends on Expression of the CCR5 Co-receptor at the Cell Surface and ENV Fusogenic Activity

Abstract: HIV-1 infections lead to a progressive depletion of CD4 cells culminating in AIDS. The coreceptor usage by HIV varies from CCR5 (R5) tropic early in infection to CXCR4 (X4) tropic in later infections. Although the coreceptor switch from R5 to X4 tropic HIV is well associated with progression to AIDS, the role of CCR5 in disease progression especially in patients infected exclusively with R5 isolates throughout the disease remains enigmatic. To better understand the role of CCR5 and R5 tropic HIV envelope in AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 70 publications
(67 reference statements)
0
53
0
Order By: Relevance
“…The mechanisms underlying this unconventional and atypical long-lasting downregulation of CCR5 required further investigation. Accordingly, in-depth analysis of the early events subsequent to the incubation of CCR5-specific Abs (CCR5 Ab pos) was performed with the T lymphoblastoid R5-SupT1-L23 cell line, which has cell surface levels very similar to those expressed in human CD4 + T lymphocytes (23). Where indicated, the majority of the key experiments were confirmed in human CD4 + T lymphocytes, which represent the natural target of HIV.…”
Section: Anti-ccr5 Abs Induce Ccr5 Internalization With Clathrinmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying this unconventional and atypical long-lasting downregulation of CCR5 required further investigation. Accordingly, in-depth analysis of the early events subsequent to the incubation of CCR5-specific Abs (CCR5 Ab pos) was performed with the T lymphoblastoid R5-SupT1-L23 cell line, which has cell surface levels very similar to those expressed in human CD4 + T lymphocytes (23). Where indicated, the majority of the key experiments were confirmed in human CD4 + T lymphocytes, which represent the natural target of HIV.…”
Section: Anti-ccr5 Abs Induce Ccr5 Internalization With Clathrinmentioning
confidence: 99%
“…To this end, we used R5-SupT1-M10 to immunoprecipitate both ERK1/2 and CCR5. R5-SupT1-M10 cells displayed a higher level of CCR5 expression than did R5-SupT1-L23 cells (23). R5-SupT1-M10 or mock cells (SupT1 not transduced with CCR5) were treated with CCR5 Ab pos for 150 min.…”
Section: Physical Association Between Erk1/2 and Ccr5mentioning
confidence: 99%
“…Four point mutations (A835W, A838W, A838I, and I842R) in the cytoplasm domain of the gp41 subunit of the envelope protein reduces HIV-induced apoptosis of target cells (Micoli et al, 2006). A recent study has shown that induction of bystander apoptosis in CCR5 expressing cells requires the fusogenic activity of gp41; and that V2E and V38A/E point mutation in the second amino acid and the heptad repeat 1 region of gp41 respectively, abrogated fusion activity and hence apoptosis induced by an R5 virus (Joshi et al, 2011). In an earlier study, the same group showed that a V513E point mutation in the fusion domain of gp41 resulted in a fusion-defective envelope protein that failed to induce apoptosis and that a G547D mutation in the gp41 N-terminal helix also reduced cell fusion capacity and apoptosis induced by an X4 virus (Garg et al, 2007).…”
Section: Point Mutations Associated With Hiv-1 Tropism Transmission mentioning
confidence: 99%
“…J. Li et al, 1995;Zhu et al, 2011). HIV-induced apoptosis is triggered by a number of HIV-1 proteins, notably the envelope protein (Herbein et al, 1998;Ishikawa et al, 1998;Joshi et al, 2011;Micoli et al, 2006;Micoli et al, 2000). Four point mutations (A835W, A838W, A838I, and I842R) in the cytoplasm domain of the gp41 subunit of the envelope protein reduces HIV-induced apoptosis of target cells (Micoli et al, 2006).…”
Section: Point Mutations Associated With Hiv-1 Tropism Transmission mentioning
confidence: 99%
See 1 more Smart Citation